Exploring the challenges of social participation during COVID-19 in Saudi Arabia through an occupational therapy lens - Meny, Areej (Frontiers in Public Health, 2024)
Aim: To measure the social participation of people in Saudi Arabia during the COVID-19 pandemic. Subject and Methods: A cross-sectional survey was conducted among people in Saudi Arabia to measure their participation in social activities during the COVID-19 pandemic. A validated questionnaire of the Social Participation Scale was used to collect data from five main regions in Saudi Arabia through social media platforms. Means, frequencies, and percentages were calculated through descriptive analysis. Mean scores and standard deviation of social participation of participants were also presented. Results: The total number of participants was 1560 including Saudi (87.3%) and non-Saudi (12.7%) nationals. Most participants (60.2%) were female. The age of participants ranged between 16-24 years old. Around 62.1% of participants were married, 63.2% were educated, 48.4 were employed and 82% were from the Eastern region. Around 72% of participants earned <10,000 riyals per month compared to those (27.3%) who earned <5000 riyals monthly. Nearly 72.7% of the participants were diagnosed with COVID-19. The mean score of social participation was 47.81 (SD=0.27). Most participants (62.7%) reported that social participation was severely restricted. Around 68.2% of the participants were quarantined at the facilities. Conclusion: The social participation of people in Saudi Arabia had been severely restricted during the COVID-19 pandemic. An early assessment of people's social participation would help to identify their problems and needs, to help them improve their involvement in social activities and thus increase their overall quality of life. Keywords: Social participation, COVID-19, participation in activities of daily living, social isolation, Saudi Arabia.